Are Immigrants More Likely Than Native-Born Americans to Perpetrate Intimate Partner Violence?. (July 2015) - Vaughn, Michael G.; Salas-Wright, Christopher P.; Cooper-Sadlo, Shannon; Maynard, Brandy R.; Larson, Matthew
Despite an emerging body of research indicating that immigrants are less likely than native-born Americans to engage in crime and antisocial behavior, less attention has focused specifically on intimate partner violence (IPV) perpetration among immigrant populations. We address this gap by using data from Wave II of the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) and compare immigrants from Asia, Africa, Europe, and Latin America to native-born Americans with respect to multiple forms of IPV. After controlling for an extensive array of confounds, results indicate that in the aggregate, immigrants are significantly more likely to perpetrate IPV. However, examination of major world regions indicates these results are driven by Latin American immigrants. Immigrants from Asia, Africa, and Europe report a lower prevalence of IPV perpetration than native-born Americans. This study extends prior research on the immigrant paradox and suggests that future studies take into account regional heterogeneity when examining IPV and other forms of violence in immigrant populations.